Graves’ Disease and Subdural Empyema Due to Pansinusitis: Case Report - Harahap, Roni Ananda Perwira; Melati Silvanni (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Background: Graves' disease is an autoimmune disease that primarily affects the thyroid gland. It may also affect multiple other organs including eyes and skin. Brain abscess and subdural empyema are serious infections that can stem from chronic suppurative diseases, congenital cardiomyopathy, consequences of head injury, or neurosurgical intervention, but the most frequently from chronic sinusitis or otitis. Case Presentation: A woman, age 22 years old, unmarried, came to the hospital with the main complaint of persistent headaches. Headache since 2 weeks ago along with fever that disappears arises without seizures. There is a lump in the neck for 3 years, and it has grown larger measuring 1x3 cm, immobile and supple. Nausea, vomiting, and decreased appetite are found. Thyroid fungtion test FT4 7.52 (0.93-1.7) ng/dL and TSH 0.01 (0.270-4.20) mIU/L. Chest X-ray: Dextrocardia and Cardiomegaly; MSCT Scan Head/Brain: conclusion: Pansinusitis and Right &; Left Mastoiditis; Ultrasound: thyroid: bilateral diffuse struma. MRI of the BRAIN with IV contrast: illustrating the subdural empyema. Treatment: Meropenem injection 2 g/24 hours, Dexamethasone injection 5mg/8 hours, Amitriptyline 2x12.5 mg, Thiamazole 1 x 20 mg, Propranolol 2 x 10 mg, PCT 3x1000 mg with pain scale monitoring. Conclusion: After being treated at the hospital for 8 days, complaints of headache began to decrease, and if the general condition was stable, the patient would be planned for a craniotomy with evacuation of an abscess in the brain.